Gypsum-based high-thermal-conductivity self-leveling mortar and preparation method thereof

By introducing phosphate cationic surfactant on the surface of aluminum nitride powder and modifying desulfurization gypsum with low temperature calcination process, the problem of insufficient thermal conductivity and dimensional stability of gypsum self-leveling mortar is solved, and gypsum self-leveling mortar with high thermal conductivity and good flatness is achieved.

CN119822772APending Publication Date: 2025-04-15JIANGSU JIBANG MATERIAL TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411963146.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing gypsum self-leveling mortar has shortcomings in thermal conductivity and dimensional stability, which can easily lead to hollowing and cracking of the leveling layer.

Method used

By introducing phosphate cationic surfactant on the surface of aluminum nitride powder, a hydrophobic protective layer is formed, and desulfurization gypsum is modified in combination with the low-temperature calcination process to prepare a gypsum-based high-thermal conductivity self-leveling mortar.

Benefits of technology

The thermal conductivity and dimensional stability of the gypsum self-leveling mortar is significantly improved, the flatness of the leveling layer is enhanced, and the hydrolysis problem of aluminum nitride is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217674480000021
    Figure BDA0005217674480000021
  • Figure BDA0005217674480000031
    Figure BDA0005217674480000031
  • Figure BDA0005217674480000041
    Figure BDA0005217674480000041
Patent Text Reader

Abstract

The invention discloses gypsum-based high-thermal-conductivity self-leveling mortar and a preparation method thereof. The gypsum-based high-thermal-conductivity self-leveling mortar is prepared from the following components in parts by mass: 80 to 98 parts of modified desulfurized gypsum, 0.2 to 10 parts of hydrophobized coated modified aluminum nitride, 1 to 50 parts of cement, 0.05 to 0.2 part of a water reducing agent, 0.05 to 0.2 part of a retarder, 0.05 to 0.2 part of a de-foaming agent and water which accounts for 40 to 60 percent of the total mass of all the powder materials, the hydrophobized coated modified aluminum nitride is obtained by introducing a phosphate salt cationic surfactant into aluminum nitride powder, and the modified desulfurized gypsum is obtained by adopting a low-temperature calcination process on dihydrate desulfurized gypsum. The gypsum-based high-thermal-conductivity self-leveling mortar prepared by the method disclosed by the invention not only has good flowability and thermal conductivity, but also has good dimensional stability, and the flatness of a leveling layer is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of inorganic building materials, in particular to a gypsum-based high-thermal-conductivity self-leveling mortar and a preparation method thereof. Background Art

[0002] Gypsum building materials are safe, comfortable, fast and environmentally friendly, and have become a world-recognized green and environmentally friendly building material widely used in developed countries. Gypsum self-leveling mortar is an innovation in my country's ground leveling materials, which plays an important role in improving the technical competitiveness of my country's construction industry, improving the overall quality of my country's construction projects, and promoting the comprehensive utilization of industrial solid waste desulfurization gypsum.

[0003] Gypsum self-leveling mortar uses semi-hydrated gypsum as its main raw material. It is a new type of floor mortar material that can automatically level with the help of the characteristics of fluid flow, has high flatness, and short setting time. Compared with traditional fine stone concrete leveling materials, gypsum self-leveling mortar has a small shrinkage rate. In addition, it saves a lot of material and labor costs and greatly shortens the construction period. In an era of rising labor costs, gypsum self-leveling mortar is more competitive in terms of economy.

[0004] With the expansion of market applications and the popularization of buried floor heating in ground leveling systems, higher requirements are placed on the thermal conductivity and dimensional stability of gypsum self-leveling mortar, otherwise it is very easy to cause hollowing and cracking problems in the leveling layer. Summary of the invention

[0005] Based on the above background technology, the present invention provides a gypsum-based high thermal conductivity self-leveling mortar and a preparation method thereof. The gypsum self-leveling mortar prepared by the method not only has good fluidity and thermal conductivity, but can also be used for filling gaps in floor heating pipes and for upper covering, greatly improving the flatness of the leveling layer while having good dimensional stability.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] A gypsum-based high thermal conductivity self-leveling mortar comprises the following components, and the mass fraction of each component is as follows:

[0008]

[0009] The amount of water used is 40-60% of the total mass of all the above powders;

[0010] The preparation method of the hydrophobic coated modified aluminum nitride is as follows: a phosphate cationic surfactant is introduced into the aluminum nitride powder to form a hydrophobic protective layer on the surface of the aluminum nitride powder, and the mass ratio of the aluminum nitride to the phosphate cationic surfactant is 10: (0.1-1);

[0011] The modified desulfurized gypsum is obtained from dihydrate desulfurized gypsum by a low-temperature calcination process, the calcination temperature is 120-160°C, and the feed rate is 15 tons / hour; the feed rate is used to control the calcination time, 15 tons per hour means 15 tons calcined in a calcination furnace for one hour. The calcination process is used to reduce the defects on the surface of the gypsum crystals, the hydration exothermic process is relatively slow, and the maximum exothermic temperature is lower than 40°C, which can effectively alleviate the decomposition problem of aluminum nitride.

[0012] Furthermore, the aluminum nitride powder of the present invention is in the form of white powder with a purity of 99.5% and a fineness of 1.0 to 10.0 μm.

[0013] Furthermore, the specific preparation method of the hydrophobic coated modified aluminum nitride of the present invention is as follows:

[0014] (1) First, aluminum nitride powder is placed in anhydrous ethanol, magnetically stirred for 1 to 3 hours, and then ultrasonically dispersed to obtain an aluminum nitride dispersion solution;

[0015] (2) dissolving a phosphate ester salt in phosphoric acid, adding anhydrous ethanol solution, and stirring at room temperature for 1 to 3 hours to obtain a phosphate ester salt cation solution, wherein the mass ratio of the phosphate ester salt to the phosphoric acid is 1:2;

[0016] (3) The phosphate ester salt cation solution obtained in the above step (2) is added to the aluminum nitride dispersion solution in step (1), stirred and ultrasonically dispersed at room temperature for 1 to 3 hours, and then the treated hydrophobic coated modified aluminum nitride is obtained through a distillation-washing-distillation process.

[0017] Since the surface of aluminum nitride is negatively charged, the addition of cationic surfactants changes the gas-liquid and solid-liquid interfacial tensions in the powder dispersion system, forming a hydrophobic coating on the powder surface, which exhibits strong hydrophobicity and effectively prevents the hydrolysis of aluminum nitride in water.

[0018] The thermal conductivity of aluminum nitride is as high as 320W / m·K. Aluminum nitride is very easy to hydrolyze to generate aluminum hydroxide and ammonia. Since the thermal conductivity of aluminum hydroxide is only 0.02-0.05W / m·K, the thermal conductivity of aluminum nitride will be significantly reduced in a water-containing material system. Therefore, in the gypsum self-leveling system, how to reduce the hydrolysis of aluminum nitride is of great significance to improving the thermal conductivity of the gypsum self-leveling system.

[0019] Furthermore, the preparation method of the gypsum-based high thermal conductivity self-leveling mortar of the present invention comprises: premixing powder-modified desulfurized gypsum, hydrophobic coated modified aluminum nitride, cement, water reducer, retarder and defoamer and then adding water and stirring to obtain the mortar.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) Aluminum nitride is modified by hydrophobic coating to exhibit strong hydrophobicity, which reduces the hydrolysis of aluminum nitride during the mortar preparation process, thereby enhancing the thermal conductivity of the gypsum self-leveling mortar;

[0022] (2) The self-leveling mortar prepared by the present invention has good fluidity and thermal conductivity, greatly improves the flatness of the leveling layer, and has good dimensional stability. DETAILED DESCRIPTION

[0023] The present invention is further described in detail below through specific implementation modes.

[0024] The amount of each component in each embodiment and comparative example is measured in parts by mass.

[0025] Table 1 shows the formulas of various embodiments and comparative examples and the calcination temperature of desulfurized gypsum. The comparative example parameters in Table 1 are the differences between comparative examples 1, 2, 3, and 4 and embodiment 1.

[0026] The modified desulfurized gypsum is obtained from desulfurized gypsum dihydrate by a low-temperature calcination process, the calcination temperature is 120-160° C., and the feed rate is 15 tons / hour.

[0027] The preparation method of the hydrophobic coated modified aluminum nitride is as follows:

[0028] (1) First, 50 g of aluminum nitride powder was placed in 200 ml of anhydrous ethanol, magnetically stirred for 2 h, and then ultrasonically dispersed to obtain an aluminum nitride dispersion solution;

[0029] (2) dissolving 1 g of phosphate salt in 2 g of phosphoric acid, adding 150 ml of anhydrous ethanol solution, and stirring at room temperature for 2 h to obtain a phosphate salt cation solution;

[0030] (3) The above-mentioned phosphate ester salt cationic solution is added to the aluminum nitride dispersion solution, and after stirring and ultrasonic dispersion at room temperature for 3 hours, a hydrophobic coated modified aluminum nitride is obtained through a distillation-washing-distillation process.

[0031] Table 1 Formulas of Examples and Comparative Examples

[0032]

[0033]

[0034] The proportions of other components in Examples 1-3 and Comparative Examples 1-4 are as follows:

[0035] Example 1

[0036] A gypsum-based high thermal conductivity self-leveling mortar is obtained by mixing the following components: 87 parts of modified desulfurized gypsum, 0.2 parts of hydrophobic coated modified aluminum nitride, 12 parts of cement, 0.15 parts of water reducing agent, 0.15 parts of retarder, 0.15 parts of defoaming agent, and the amount of water accounts for 43% of the total mass of the powder.

[0037] Example 2

[0038] A gypsum-based high thermal conductivity self-leveling mortar is obtained by mixing the following components: 85 parts of modified desulfurized gypsum, 2 parts of hydrophobic coated modified aluminum nitride, 12 parts of cement, 0.15 parts of water reducer, 0.15 parts of retarder, 0.15 parts of defoamer, and the amount of water accounts for 43% of the total mass of the powder.

[0039] Example 3

[0040] A gypsum-based high thermal conductivity self-leveling mortar is obtained by mixing the following components: 85 parts of modified desulfurized gypsum, 10 parts of hydrophobic coated modified aluminum nitride, 4 parts of cement, 0.15 parts of water reducer, 0.15 parts of retarder, 0.15 parts of defoamer, and the amount of water accounts for 42% of the total mass of the powder.

[0041] Comparative Example 1

[0042] A self-leveling mortar is obtained by mixing the following components: 87 parts of modified desulfurized gypsum, 12 parts of cement, 0.15 parts of a water reducing agent, 0.15 parts of a retarder, 0.15 parts of a defoaming agent, and the amount of water used accounts for 45% of the total weight of the powder.

[0043] Comparative Example 2

[0044] A self-leveling mortar is obtained by mixing the following components: 85 parts of modified desulfurized gypsum, 2 parts of unmodified aluminum nitride, 12 parts of cement, 0.15 parts of a water reducing agent, 0.15 parts of a retarder, 0.15 parts of a defoaming agent, and the amount of water used accounts for 43% of the total weight of the powder.

[0045] Comparative Example 3

[0046] A self-leveling mortar is obtained by mixing the following components: 85 parts of modified desulfurized gypsum, 2 parts of aluminum hydroxide, 12 parts of cement, 0.15 parts of water reducing agent, 0.15 parts of retarder, 0.15 parts of defoaming agent, and the amount of water accounts for 45% of the total weight of the powder.

[0047] Comparative Example 4

[0048] A self-leveling mortar is obtained by mixing the following components: 85 parts of unmodified desulfurized gypsum, 2 parts of hydrophobic coated modified aluminum nitride, 12 parts of cement, 0.15 parts of water reducing agent, 0.15 parts of retarder, 0.15 parts of defoaming agent, and the amount of water used accounts for 45% of the total weight of the powder.

[0049] Mixing method of gypsum self-leveling: After pouring appropriate amount of water into the mixer, pour the powder into the mixer at a uniform speed within 30 seconds, and mix at a low speed for 60 seconds; stop stirring, and use a scraper to scrape off the uneven mixture on the stirring blades and the wall of the material pot within 30 seconds; stir at high speed for 60 seconds, stop for 60 seconds, and continue to stir at high speed for 15 seconds to obtain a uniformly mixed gypsum self-leveling mortar; the appropriate amount of water refers to the amount of water used when the fluidity is between 140-150mm through the fluidity test.

[0050] In the present invention, the thermal conductivity adopts the transient plane heat source method, and the thickness and size of the test block of this method are irrelevant to the measurement results; the test block size of absolute dry shrinkage and absolute dry compressive strength is 40*40*160mm, and the test block is cured for 28 days under the conditions of humidity 65±5% and temperature 23±5℃, and then dried in an oven at 40℃ to absolute dryness to obtain the data; the 30min fluidity loss is the difference between the fluidity measured by standing the slurry that meets the initial fluidity in a mixing bowl for 30min and then stirring for 30s and the initial fluidity; the measurement of absolute dry tensile bond strength adopts a concrete test block that meets JC / T547-2017, and the test block size has an outer frame size of 70*70mm, an inner frame size of 50*50mm, and a thickness of 5mm. After the test block is cured for 28 days under the conditions of humidity 65±5% and temperature 23±5℃, it is dried in an oven at 40℃ to absolute dryness to measure the tensile bond strength.

[0051] Table 2 Performance of gypsum self-leveling mortar in each embodiment and comparative example

[0052]

[0053]

[0054] It can be found from the data in Table 2 that, in Example 1-Example 3, as the amount of hydrophobic coated modified aluminum nitride added increases, the thermal conductivity shows an increasing trend; compared with Comparative Example 1, the thermal conductivity of the three groups of examples is significantly improved after the modified aluminum nitride is added; comparing Example 2 and Comparative Example 2, under the same dosage, the thermal conductivity of the aluminum nitride modified by hydrophobic coating is higher than that of the unmodified aluminum nitride, and the modified aluminum nitride can effectively reduce the hydrolysis problem of aluminum nitride; after adding aluminum hydroxide to Comparative Example 3, the thermal conductivity is almost the same as that of the unadded group, and aluminum hydroxide does not help to improve the thermal conductivity; the calcination temperature of Comparative Example 4 is relatively high, and there are many defects on the surface of the desulfurized gypsum, and the hydration temperature can reach up to 60°C, while the hydration temperature of the gypsum powder calcined in Examples 1-3 can reach up to 45°C, and the gypsum powder calcined at a low temperature has a low exothermic temperature, which can effectively reduce the hydrolysis of aluminum nitride, thereby improving the thermal conductivity of the entire system.

[0055] The absolute shrinkage rate of Examples 1-3 is 0.02%. The hydrophobic coated modified aluminum nitride is also helpful to improve the volume stability of the gypsum self-leveling mortar. Moreover, the hydrophobic coated modified aluminum nitride can appropriately improve the flow properties of the gypsum self-leveling mortar, and has no adverse effect on the absolute dry compressive strength and the absolute dry tensile bond strength.

[0056] By testing the pH value, the pH value of the unmodified aluminum nitride added directly in Comparative Example 2 was 10.5, which was very close to the pH value of 10.8 of the aluminum hydroxide added directly in Comparative Example 3; and the pH value of the hydrophobic modified aluminum nitride added in Examples 1-3 was 8.7, which was close to the pH value of 8.5 of the blank group in Comparative Example 1. This shows that the hydrolysis problem of aluminum nitride is significantly improved by hydrophobic modified aluminum nitride.

Claims

1. A gypsum-based high thermal conductivity self-leveling mortar, characterized in that: It includes the following components, and the mass fractions of each component are as follows: The amount of water used is 40-60% of the total mass of all the above powders; The preparation method of the hydrophobic coated modified aluminum nitride is as follows: a phosphate cationic surfactant is introduced into the aluminum nitride powder to form a hydrophobic protective layer on the surface of the aluminum nitride powder, and the mass ratio of the aluminum nitride to the phosphate cationic surfactant is 10: (0.1-1); The modified desulfurized gypsum is obtained from desulfurized gypsum dihydrate by a low-temperature calcination process, the calcination temperature is 120-160° C., and the feed rate is 15 tons / hour.

2. The gypsum-based high thermal conductivity self-leveling mortar according to claim 1, characterized in that: The aluminum nitride powder is in the form of white powder with a purity of 99.5% and a fineness of 1.0 to 10.0 μm.

3. The gypsum-based high thermal conductivity self-leveling mortar according to claim 1 or 2, characterized in that: The specific preparation method of the hydrophobic coated modified aluminum nitride is as follows: (1) First, aluminum nitride powder is placed in anhydrous ethanol, magnetically stirred for 1 to 3 hours, and then ultrasonically dispersed to obtain an aluminum nitride dispersion solution; (2) dissolving a phosphate ester salt in phosphoric acid, adding anhydrous ethanol solution, and stirring at room temperature for 1 to 3 hours to obtain a phosphate ester salt cation solution, wherein the mass ratio of the phosphate ester salt to the phosphoric acid is 1:2; (3) The phosphate ester salt cation solution obtained in the above step (2) is added to the aluminum nitride dispersion solution in step (1), stirred and ultrasonically dispersed at room temperature for 1 to 3 hours, and then the treated hydrophobic coated modified aluminum nitride is obtained through a distillation-washing-distillation process.